Kiai Pesantren dalam Politik Pendidikan Islam - Moh. Ismail (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose: This study aims to map the dynamics of pesantren kiai involvement in Islamic education politics in Bangkalan Regency, examining the patterns of engagement and factors influencing their participation in educational policy formulation. Design/methodology/approach: Using a qualitative-descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation studies involving kiai, public officials, and community leaders in Bangkalan Research limitations/implications: The study is limited to Bangkalan Regency and may not be generalizable to other regions. The findings suggest the need for formalized synergy mechanisms between pesantren and local government in education policy-making. Findings: The relationship between kiai and public officials is mutualistic with patronage characteristics. Kiai involvement is classified into three patterns: active, moderate, and traditional, with dominant influence in socio-cultural domains rather than formal political structures. Factors such as pesantren characteristics, personal charisma of kiai, and local Islamic education issues significantly affect involvement levels. Originality/value: This research contributes to understanding the strategic role of kiai in Islamic education policy formulation in regional contexts, particularly in areas with strong pesantren traditions, and proposes collaborative frameworks for inclusive education policy development.